A Scoping Review in Indian Post-Stroke Patients - Pandita, Rajesh; Patel, Rachna (Scripta Medica, 2023)
Stroke is the second most common cause of death worldwide and the third most common cause of disability-adjusted life years (DALYs) worldwide. According to the available evidence, 85.5 % of total stroke fatalities are reported in low- and middle-income countries compared with high-income countries. In addition, the prevalence of DALYs in low-income countries is very high. The major challenge is the vastness of India and its humongous population size, which makes it nearly impossible to reach patients far away. The quality of life (QoL) of stroke survivors is an important factor in predicting the burden of the disease and determining the effectiveness of treatment. Many research studies provide an overview of the overall estimates of QoL and contribute to research on QoL after stroke in India. Owing to the bleak post-stroke rehabilitation facilities in India, stroke patients don’t get the post-stroke care they ought to. The gap is not only in the patient care management system but also in the policies laid out by the government. The unmet gaps in post-stroke rehabilitation and patient care remain a major setback in patient care management, which impacts the clinical outcomes at large. These challenges are the reasons for the increasing disease burden on society and the hampering of the socio-economic status of the country at large. The government authorities should lay down the policy that will help the patient seek the correct in-time treatment for stroke and help the post-stroke patients to live a QoL.
Keywords: Quality of life; Rehabilitation; Post-stroke rehabilitation; Patient care management; Patient education